Prototype Mesin Pengantar Barang Otomatis Menggunakan Load Cell Berbasis Robot Line Follower - Susilo, Dwi Budi; Wibawanto, Hari; Mulwinda, Anggraini (Jurnal Teknik Elektro, 2018)
Overloaded condition in the product porter like hand pallet, hand stacker, forclift, and etc, can causes damage and terrible accident in the machine operator. This research aim to build a prototype of porter machine that can prevent overloaded condition through the reading of load cell and photo diode sensor to guide the line follower direction. Research and development methods are used with the systematic writing are background of study and problems, prototype design and validation, testing, taking and analysis of the data. Output of the research is a prototype of porter machine using load cell sensor based on line follower robot. The Result of the load cell reading is compared to SF-400 weigher, and found the difference amount 0.117%. The load testing data of automatic moving trigger is 1 gram until 2999 gram. The Overload condition warning is active while the load is more than 3000 gram. The data reading of the photo diode on the black line is running succesfully, however on the white line with orange color is found some error.